2004
DOI: 10.1046/j.0001-6772.2003.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Clenbuterol treatment affects myosin heavy chain isoforms and MyoD content similarly in intact and regenerated soleus muscles

Abstract: These results show that regenerated soleus muscles, comprising a homogeneous population of fibres deriving from satellite cells, have a similar response to clenbuterol as intact muscle arising from at least two discrete populations of myotubes; it is suggested that the activity of signalling pathways involved in the effects of clenbuterol on MHC transitions is not related to the developmental history of myofibres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 36 publications
0
21
0
7
Order By: Relevance
“…This delicate balance suggests that hypertrophy may provide a means to antagonize skeletal muscle atrophy induced by some physiological and pathological challenges (16). ␤-Adrenergic agonists (BA) are a family of compounds that induce skeletal muscle hypertrophy in rats (7,13,46), mice (21), pigs (12), cattle, and sheep (27). Consistent with the aforementioned thesis, BA antagonize skeletal muscle atrophy in experimentally induced denervation or limb immobilization models (11,21).…”
mentioning
confidence: 60%
“…This delicate balance suggests that hypertrophy may provide a means to antagonize skeletal muscle atrophy induced by some physiological and pathological challenges (16). ␤-Adrenergic agonists (BA) are a family of compounds that induce skeletal muscle hypertrophy in rats (7,13,46), mice (21), pigs (12), cattle, and sheep (27). Consistent with the aforementioned thesis, BA antagonize skeletal muscle atrophy in experimentally induced denervation or limb immobilization models (11,21).…”
mentioning
confidence: 60%
“…Evidence comes from the findings of Beitzel et al (31) and Bricout et al (57) who found that administration of a ␤-agonist hastened the functional recovery of regenerating rat skeletal muscles after myotoxic injury with bupivacaine or Notexin, respectively. Daily fenoterol administration to rats (1.4 mg⅐kg Ϫ1 ⅐day Ϫ1 ip) enhanced the force-producing capacity of the injured/regenerating EDL muscles by 19% compared with untreated regenerating muscles at 14 days postinjury.…”
Section: F Improving Muscle Regeneration and Functional Repair Aftermentioning
confidence: 97%
“…[35][36][37][38][39] Among these durations, we selected the most prolonged period, and demonstrated that such stimuli suppresses the phagocytic activity of splenic adherent cells expressing high levels of MARCO. It is necessary to elucidate the mechanisms of β 2 -agonist action by examining in various periods, including the acute experiment.…”
Section: Discussionmentioning
confidence: 99%